Income and Wealth Imputation for Waves 1 and 2 - Watson, N (Melbourne Institute of Applied Economic and Social Research, 2004)
All surveys are confronted with the problem of non-response. In an earlier discussion paper, Watson and Wooden (2003) assessed the non-response problem in the HILDA Survey, reviewed various methods for dealing with the missing data, and proposed an imputation strategy. This strategy has been largely adopted for Release 2.0 of the HILDA data. The scope of the imputation has been extended beyond income imputation to include the imputation of the wealth variables that were collected in wave 2. The purpose of this paper is to detail the imputation method used, and discuss the quality of the resulting imputation.
HILDA Project Technical Paper Series
Keywords: Surveys and Survey Methodology -- Dataset cleaning and development; Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Dataset cleaning and development; Surveys and Survey Methodology